THE PROPOSED MARKETING DEPARTMENT FOR MISAN OLYMPIC STADIUM - Hussein Karim Hassoun (Proximus Journal Publishing, 2024)
The globe is seeing progress in investment and sports marketing, supported by considerable research in investment and commercial propositions. The phrase refers to the need of doing research on a marketing proposition for Misan Olympic Stadium. Marketing Olympic Marketing Arena Definition of Marketing: Distribution and Services in Marketing Research Methodologies Initially: The researcher used a descriptive technique. Utilising the survey methodology. Direct: the research community and the research cohort: The study community included a random selection of 48, derived from a direct selection of 37. The first recommendations: Initial evaluations: Announcing the offerings of Misan Olympic Stadium. The General Department of Marketing constitutes the administrative organisational framework of Basra Sports City. Implementing job descriptions for administrative positions and incorporating them into the organisational framework
Keywords: Marketing Department; Misan; Olympic Stadium